2018
DOI: 10.1007/s10096-018-3352-1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and later impacts of antimicrobial consumption on carbapenem-resistant Acinetobacter spp., Pseudomonas aeruginosa, and Klebsiella spp. in a teaching hospital in Brazil: a 10-year trend study

Abstract: To evaluate trends and the immediate and late impact of antimicrobial consumption on carbapenem-resistant Acinetobacter spp. (CRAs), carbapenem-resistant Pseudomonas aeruginosa (CRPA), and carbapenem-resistant Klebsiella spp. (CRKs) over a 10-year period. An ecological study was conducted at the teaching hospital in São Paulo, Brazil, from 2007 to 2016. Consumption and resistance data were collected from the supply sector and central laboratory of the institution, respectively. Associations between consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[18] The increase of resistance rate of carbapenems may be related to the unreasonable use of carbapenems. [19] Therefore, the control of carbapenem resistant K. pneumoniae in our hospital was the top priority for infection control. Distribution of main pathogens in lower respiratory tract infection (n > 100)…”
Section: Discussionmentioning
confidence: 99%
“…[18] The increase of resistance rate of carbapenems may be related to the unreasonable use of carbapenems. [19] Therefore, the control of carbapenem resistant K. pneumoniae in our hospital was the top priority for infection control. Distribution of main pathogens in lower respiratory tract infection (n > 100)…”
Section: Discussionmentioning
confidence: 99%
“…An ecological study conducted at teaching hospitals in Brazil from 2007-2016 showed that increase consumption of β-lactam/β-lactamase inhibitors increased the frequency of carbapenem-resistant Klebsiella spp. with a 1-year time delay [25]. Indeed, increased usage of third-generation cephalosporins was found to be the main independent risk factors of CRKP infections in a retrospective cohort study done in Turkey [26].…”
Section: Discussionmentioning
confidence: 99%
“…[18] The increase of resistance rate of carbapenems may be related to the unreasonable use of carbapenems. [19] Therefore, the control of carbapenem resistant K. pneumoniae in our hospital was the top priority for infection control.…”
Section: 9% (Fig 1)mentioning
confidence: 99%